2018
DOI: 10.1016/j.asoc.2017.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Distributed evolutionary algorithm for co-optimization of building and district systems for early community energy masterplanning

Abstract: Buildings play a significant role in climate change mitigation. In North America, energy used to construct and operate buildings accounts for some 40% of total energy use, largely originating from fossil fuels [1]. The strategic reduction of these energy demands requires knowledge of potential upgrades prior to a building's construction. Furthermore, renewable energy generation integrated into buildings faç ades and district systems can improve the resiliency of community infrastructure. However, loads that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…4 shows, cost minimization is the most frequent objective and is considered for more than 90% of studies while even the second most common objective, CO 2 emissions, is only present in less than a third of all studies. Other objectives such as a minimization of primary energy consumption [126,128] or non-renewable energy consumption [141] or a maximization of self-generation [142] are only encountered in individual examples.…”
Section: Tablementioning
confidence: 99%
“…4 shows, cost minimization is the most frequent objective and is considered for more than 90% of studies while even the second most common objective, CO 2 emissions, is only present in less than a third of all studies. Other objectives such as a minimization of primary energy consumption [126,128] or non-renewable energy consumption [141] or a maximization of self-generation [142] are only encountered in individual examples.…”
Section: Tablementioning
confidence: 99%
“…Unsupervised classification over large-scale datasets has also been tackled by adopting dEAs, such as [221], where an island genetic algorithm is proposed for fuzzy partition problems, or [222], where dEAs are applied to improve a k-Means clustering algorithm. There has been also active research around more practical versions of dEAs, in areas such as large-scale optimization [223,224,225], Electromagnetism [226], Computational Fluid Mechanics [227], energy planning [228] or neural networks training [229].…”
Section: Distributed Evolutionary Algorithmsmentioning
confidence: 99%
“…Hence, the ultimate goal of sustainable development in smart buildings is to enhance energy efficiency by minimizing energy losses and environmental impacts. In particular, renewable energy generators can be built into buildings and district infrastructure to boost the sustainable community [47,66]. The discussed BEMS is also known as a nearly or net-zero energy building (nZEB) [8].…”
Section: Smart Buildingmentioning
confidence: 99%
“…In addition, BA, which is a SI approach inspired by the properties of bats in echolocation, was used in [72], and an ensemble of GA and PSO was used in [74]. Beyond the scale of buildings, Bucking et al [66] suggested an approach to co-optimize buildings and community energy networks to minimize energy utilization and stabilize the loads. The dEA algorithm was introduced to help communities achieve net-zero energy and alleviate peaks applying a district energy system at the same time.…”
Section: Smart Buildingmentioning
confidence: 99%